IMPLEMENTASI LOGIKA FUZZY PADA PEMBUATAN KARAKTER MUSUH UNTUK GAME SINGLE FIGHTER BERPLATFORM ANDROID - Fajar Mitasari; Wawan Laksito Yuly Saptomo; Sri Siswanti (STMIK Sinar Nusantara, 2017)
This adventure game tells the story of an elephant who struggles to save his son from enemy prisoners. Elephants should be able to beat all three enemies, namely monkeys, wolves, and kingkong to be able to find his son. In the course of fighting the enemy will be no relief in the form of bombs and weapons are power ups in the form of apples to increase the number of lives player. The behavior of the enemy characters in this game are designed with the application of fuzzy logic Sugeno method. Each enemy by artificial intelligence has a health status (lives), ammo (the number of stones to attack the player) and distance (distance to the player during the attack). This game has a rule of implementation Sugeno Fuzzy Logic method for calculating the value of output behavior of the enemy in attacking player. The system design of the game is using the storyboard that contains a description of the story of each scene and any component material that will be used. Then the algorithm implementation using the Unity game development software. For game development, programming language used is C # of Unity. The results of this study are the Application Game